Estudo das luminescências de íons terras raras incorporados na matriz vítrea Aluminosilicato de Cálcio - Udo, Paulo Toshio (2008)
In this work we studied the potentiality for technological applications in optical devices, both active and passive, of the hydroxyls free low silica calcium aluminosilicato glasses (LSCAS) doped with trivalent rare earth ions. We produced glasses doped with ytterbium, ytterbium and thulium and ytterbium and holmium. The results showed the possibility of using these systems as active media for lasers operating from the near to mid-infrared spectral regions for practical application in the biomedical and odontological areas and in the visible and near infrared for data transmission system by switching the intensities of the luminescence of the trivalent thulium at λ=480 and λ=800 nm. The samples were produced in a controlled melting system in reductive atmosphere, maintained by a vacuum system to eliminate the formation of hydroxyl and thereby to obtain an active medium with optical transparency of the order of 90% in the region from the visible to mid-infrared, up to 5 μm. Thus, the luminescence of the rare earth ions incorporated into the vitreous matrix are not re-absorbed, allowing the production the active medium for solid state laser to operate in this region of the spectrum. The characterization of the samples was done with thermal lens spectrometry, optical absorption and photoluminescence. To achieve efficient emission at 1,8 μm we studied the relation between the concentration of the Yb3+ and Tm3+ ions with the pump power regime to promote the mechanisms of energy transfer to this emission. To determine the quantum efficiency of the emission at 1.8 μm in the system doped with ytterbium and thulium, the method employed by Rohling, considering the branching ratio of the transitions between metastable levels of the trivalent thulium, was extended. Moreover, the system doped with Yb3+ and Tm3+ showed dependence on the intensity ratio of luminescent emission at 480 and at 800 nm due to Tm3+ concentration and pumping power laser, presenting a switch in the luminescence intensities in those wavelengths. This result shows a technological potential of these glasses to be used in devices for optical information transmission. Preliminary studies of glass LSCAS doped with Yb3+and Ho3+ indicate a potential for development of active medium for solid state lasers with emission in the mid-infrared spectral region, complementing the Yb3+ and Tm3+ system. We also produced for the first time the LSCAS glass doped with TiO2 which presents a long fluorescence life time, on the order of 170 μs. Preliminary studies indicate a potential for the development of active medium for laser with spectral emission of Ti3+ near that of commercial Ti-sapphire, but because of the special properties of the LSCAS vitreous matrix, it may expand the spectral and the power scales beyond those achieved with crystalline matrix Ti3+: Al2O3, similarly to the system Nd: YAG and Nd: Glass. In conclusion, the results of this study indicate the possibility of expanding the use of LSCAS vitreous matrix as a host for active ions for the development of passive optical devices and active medium for laser operating in the spectral region from the visible to mid infrared.